International Prolonged Grief Disorder Scale Addendum for Refugees and Displaced People (IPGDS-ARD): A Study of Arabic-Speaking Bereaved Refugees - Clare Killikelly; Alexandra Reymond; Anaïs Aeschlimann; Andreas Maercker; Eva Heim (Clinical Psychology in Europe)
[Background] Prolonged grief disorder (PGD) is a new and significant addition to the ICD-11 WHO disease classification system and the DSM 5-TR. As a new disorder, it stands to improve diagnostic precision, enhance communication among health professionals and patients, provide better access to care and lead to effective treatments and intervention. However, it remains to be determined if the new diagnostic criteria for PGD are applicable to different cultural groups. [Method] Here we sought to adapt the International Prolonged Grief Disorder Scale for refugees and displaced people. We conducted two focus groups with clinicians and health care workers and six cognitive interviews with bereaved Arabic-speaking refugees. [Results] This formative research resulted in an addendum (comprised of three new scales) to the IPGDS aimed to aid with treatment planning: the 42 item Addendum for Refugees and Displaced people (IPGDS-ARD). Here we present the steps for scale augmentation based on cultural considerations, a detailed description of clinical utility, feasibility and content validity established at each step, and an analysis of the percent of change in content at each step. [Conclusion] We conclude that the presented method of scale augmentation is a feasible and efficient approach that led to a culturally relevant, clinically useful addendum to an existing PGD questionnaire.